Aktivitas Pedagang Fisik Aset Kripto Tidak Bersertifikat: Studi Perlindungan Hukum Bagi Investor - Shellma Riyaadhotunnisa; Muhamad Amirulloh; Deviana Yuanitasari (CV. Social Politic Genius (SIGn), 2022)
This study examines and analyzes the legal protection for Investors from the activities of uncertified crypto asset physical Traders. This study uses a normative juridical research method with a statute approach. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods. The results show that the Government has provided legal protection for investors from the activities of uncertified crypto asset physical traders based on Law No. 10 of 2011, CoFTRA Regulation No. 8 of 2021, and CoFTRA Regulation No. 11 of 2022. The crypto asset investment mechanism regulated in these laws and regulations is a form of preventive legal protection. In contrast, there is not a single CoFTRA Regulation that contains provisions on repressive legal protection for Investors suffering losses from uncertified Traders. However, Investors suffering losses from uncertified Traders can still take several legal actions: deliberation, civil lawsuit, and restorative justice on the criminal decision. Therefore, it is recommended for Investors to conduct crypto asset transactions with Traders by obtaining a registration certificate from CoFTRA. In addition, it is recommended to CoFTRA for more regulation on dispute resolution for Investors suffering losses from uncertified Traders. In this case, to create legal certainty and better legal protection in future crypto asset physical market trading.